Guest Editorial: the Many Facets of Port Development - Ligteringen, Han; Vellinga, Tiedo (European Journal of Transport and Infrastructure Research, 2012)
In June 2010 a seminar was organised at Delft University of Technology on recent developments in the field of Ports and Waterways. During the seminar 36 papers were presented and discussed, both academic and more practical oriented. It was intended from the outset to publish a selection of the more academic papers in a special issue of EJTIR, which has resulted in this issue, comprising four papers covering very different areas within the field of ports and waterways.